Breadwinners in a broken state : the feminization of economic survival in contemporary Lashio Town, Myanmar - Mya Oo Khin; Chatterjee, Joyee S.; Kusakabe, Kyoko; Roy, Joyashree; Deutscher Akademischer Austausch Dienst (DAAD), Germany (Pathum Thani, Thailand : Asian Institute of Technology, 2026)
This thesis examines the "feminization of economic survival" in contemporary Lashio Town, Myanmar, specifically focusing on women in female-headed households (FHHs) who have become primary breadwinners following the 2021 military coup and the COVID-19 pandemic. Utilizing the theoretical frameworks of Feminization of Survival and Feminist Political Economy, the research investigates how 23 de jure and de facto female household heads adapt their livelihoods amidst state failure and socio-economic collapse. The study employs a qualitative methodology, triangulating data from in-depth interviews with perspectives from three key informants to capture the lived realities of these women. The findings reveal that FHHs face a landscape of interlocking structural constraints, including hyperinflation, conflict-induced asset loss, and restricted mobility due to rising crime. A central contribution of the study is the identification of a Care-Income-Debt Cycle, where the withdrawal of public services forces women to absorb intensive care responsibilities while relying on high-interest informal debt to manage family survival. Adaptive strategies are characterized by "multi-earning" and extreme livelihood diversification within precarious informal sectors, often involving home-based work to balance the demands of sick or elderly dependents. Furthermore, the research documents a severe "dual burden," as women perform overlapping visible (paid) and invisible (unpaid) labour for 12 to 17 hours daily, leading to chronic time poverty and physical exhaustion. The study concludes that while women exhibit significant resilience, their role as breadwinners in a "broken state" is driven by necessity and self exploitation rather than empowerment. These insights provide a vital foundation for developing gender-responsive humanitarian interventions that address the unique vulnerabilities of urban and peri-urban FHHs in Myanmar's ongoing crisis.
A thesis submitted in patial fulfillment of the requirements for the degree of Master of Science in Gender and Development Studies
Thesis (M. Sc.) - Asian Institute of Technology, 2026
Keywords: Women -- Economic conditions -- Myanmar; Women -- Political aspects -- Myanmar